The use of microgravity technique in archaeology: A case study from the St. Nicolas Church in Pukanec, Slovakia - PÁNISOVÁ, Jaroslava; PAŠTEKA, Roman (Contributions to Geophysics and Geodesy, 2009)
The  detection  of subsurface cavities,  such  as  crypts, cellars  and  tunnels,  in churches  and castles  belongs to successful applications of the employment of surface  gravity measurement techniques in archaeo-prospecting.  The old historic  building  exploration requires  using of non-invasive methods, and  hence the microgravity technique is a proper candidate for this task. On a case study from the Roman-Catholic Church of St. Nicolas in  the town  Pukanec the results  of using  microgravity for detection  and  delineation of local density variations caused  by a near-surface void are  shown.  The  acquired negative anomaly in the residual  Bouguer  anomalies ﬁeld suggested the presence  of a possible void feature. Euler deconvolution and 3D modelling  were used to estimate the depth and shape of the  anomalous source.  Additionally, measurements of the vertical gravity gradient on several  stations were performed.  We tested how the  use of a downward continuation  of gravity, utilizing  the real vertical gravity gradient, inﬂuences  the  shape  and  amplitude of the ﬁnal Bouguer  anomaly map.